O estresse do trabalho e o profissional de saúde: discutindo a Síndrome de Burnout e fatores associados na atenção primária à saúde da rede SUS/Belo Horizonte - Túlio Eugênio de Souza (2018)
Introduction: Occupational stress can impair the performance of the health professional in the execution of work tasks and his occupational health. Burnout Syndrome (BS) is a subtype of stress that has been much studied in the last decades. It is structured in three dimensions: emotional exhaustion, depersonalization and reduced personal accomplishment. Objectives: To evaluate the occurrence of Burnout Syndrome and associated factors among health professionals of the Primary Health Care from the Brazilian Health System (SUS) of the city of Belo Horizonte. Methods: A quantitative cross-sectional study was conducted using a semi-structured questionnaire (self-administered and anonymous) carried out in 45 basic health units of the 152 basic health units (UBS) of nine districts in the city of Belo Horizonte, with a probabilistic sample by single-stage conglomerate. Professional Burnout was detected by Maslach Burnout Inventory. The collected data were stored in the software Statistical Package for the Social Sciences (SPSS), version 17.0. The data evaluation included univariate, bivariate and logistic regression analyzes. The project was submitted to the Research Ethics Committee and the consent of the professionals was obtained through a free and informed consent form. There was no remuneration for participants and no other conflict of interest. Results: The lack of consensus in the literature regarding the diagnostic criteria for Burnout Syndrome is visible in the estimated prevalence when considering changes in the high level in the three dimensions (Model 3) of burnout (3.3%), two (Model 2: 15.8%) and at least one (Model 1: 55.3%) among the 1,042 participating professionals. Based on the ROC curve and its area, it appears that the diagnostic pattern of Model 3 presents itself as the best diagnostic method among the three diagnostic patterns of BS, although the other two models are still useful. In the final models of logistic regression, there is an association of BS, based on Model 3, with the variables: job dissatisfaction, conflicts at work, opinion on non-compliance with schedules and non-participation in the Local Health Commission. Conclusions: The study comprises a probabilistic sample that includes the points of a primary and representative care network, addresses three diagnostic models of BS and associated variables, proposing, in addition to the classic diagnosis (Model 3), to list possible initial frames that can be alert to possible as possible before the SB picture itself. Among the diagnostic models, there is an overlap of variables that are not incongruent with the literature or like model 3. In addition, a lot of studies work with Model 1. To the detriment of the methodological limitations of a cross-sectional study, other studies are necessary to explore the determinants of burnout, serial evaluations and even direct interviews with professionals, for example; as well as research with the objective of listing intervention projects in the environment of those who are the main route to access SUS and deal directly with the assistance and care of the population.